Alterations Of Glycerophospholipid And Fatty Acyl Metabolism In Multiple Brain Regions Of Schizophrenia Microbiota Recipient Mice - Liang W (Dove Medical Press, 2019)
Weiwei Liang,1–3,* Yu Huang,1,3,* Xunmin Tan,1,3,* Jing Wu,3,4 Jiajia Duan,3,4 Hanping Zhang,1,3 Bangmin Yin,1,3 Yifan Li,1,3 Peng Zheng,1,3 Hong Wei,5 Peng Xie1,3 1Department of Neurology, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of China; 2Department of Neurology, Yongchuan Hospital, Chongqing Medical University, Chongqing 402460, People’s Republic of China; 3Institute of Neuroscience and the Collaborative Innovation Center for Brain Science, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 4The M.O.E. Key Laboratory of Laboratory Medical Diagnostics, The College of Laboratory Medicine, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 5Precision Medicine Institute, The First Affiliated Hospital, Sun Yat-Sen University, Guangzhou, Guangdong 510080, People’s Republic of China*These authors contributed equally to this workCorrespondence: Peng XieDepartment of Neurology, The First Affiliated Hospital of Chongqing Medical University, 1 Youyi Road, Yuzhong District, Chongqing 400016, People’s Republic of ChinaTel +86-23-68485490Fax +86-23-68485111Email xiepeng@cqmu.edu.cnBackground: Schizophrenia is a debilitating psychiatric disorder characterized by molecular and anatomical abnormalities of multiple brain regions. Our recent study showed that dysbiosis of the gut microbiota contributes to the onset of schizophrenia-relevant behaviors, but the underlying mechanisms remain largely unknown.Purpose: This study aimed to investigate how gut microbiota shapes metabolic signatures in multiple brain regions of schizophrenia microbiota recipient mice.Methods: Gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS) were used to compare the metabolic signatures in the cortex, cerebellum and striatum of schizophrenia microbiota and healthy microbiota recipient mice. Enrichment analysis was further conducted to uncover the crucial metabolic pathways related to schizophrenia-relevant behaviors.Results: We found that the metabolic phenotypes of these three regions were substantially different in schizophrenia microbiota recipient mice from those in healthy microbiota recipient mice. In total, we identified 499 differential metabolites that could discriminate the two groups in the three brain regions. These differential metabolites were mainly involved in glycerophospholipid and fatty acyl metabolism. Moreover, we found four of fatty acyl metabolites that were consistently altered in the three brain regions.Conclusion: Taken together, our study suggests that alterations of glycerophospholipid and fatty acyl metabolism are implicated in the onset of schizophrenia-relevant behaviors, which may provide a new understanding of the etiology of schizophrenia.Keywords: schizophrenia, gut microbiota, metabolomics, glycerophospholipids, fatty acyls, fecal microbiota transplantation